Self-Care Processes as Predictors of Quality of Life in Adults With Moyamoya Disease: A Structural Equation Modeling Study - Jeongwon Yeom; In-Sun Yeom (Research and Theory for Nursing Practice, 2026)
Background: Moyamoya disease is a chronic cerebrovascular condition requiring ongoing self-management to prevent complications. Riegel’s theory of self-care in chronic illness posits that factors such as disease knowledge, self-efficacy, social support, and access to care influence self-care maintenance, monitoring, and management, which in turn affect health outcomes and quality of life (QoL). Aim: To test a structural equation model of factors influencing self-care and outcomes in adults with moyamoya disease based on Riegel’s self-care theory. Methods: A cross-sectional survey of 211 adults with moyamoya disease collected data on disease knowledge, self-efficacy, social support, access to care, self-care maintenance, monitoring, management, health status, and QoL (Korean version of the 12-Item Short Form Health Survey). Structural equation modeling was performed using IBM SPSS Statistics 30.0 and AMOS 30.0 to test the hypothesized model. Results: The proposed model demonstrated good fit. Disease knowledge, self-efficacy, social support, and access to care were significantly associated with self-care maintenance, monitoring, and management. These self-care processes, in turn, were positively related to better health status and higher QoL. The model explained a substantial proportion of variance in health status and QoL. Conclusion: The findings support the applicability of Riegel’s self-care theory in moyamoya disease. Interventions to enhance patients’ disease knowledge, self-efficacy, social support, and access to care may improve self-care and ultimately lead to better health outcomes and QoL in this population.